Prognostic Significance of the Controlling Nutritional Status (CONUT) Score in Patients with Muscle-Invasive Bladder Cancer after Radical Cystectomy - Yücel, Cem; Dumanli, Enes; Karabacak, Mahmut Can; Akbay, Esat Kaan; Yoldas, Mehmet; Micoogullari, Uygar; Ilbey, Yusuf Ozlem; Keskin, Mehmet Zeynel (Urology Journal, 2024)
Purpose: To assess the impact of the The Controlling Nutritional Status (CONUT) score, an indicator of nutritional status, on the survival and prognosis after radical cystectomy. Materials and Methods: The medical records of patients who underwent consecutive radical cystectomy operations with the diagnosis of muscle-invasive bladder cancer at our clinic were retrospectively examined. The patients were separated into two groups based on the cut-off CONUT score which was derived using the receiver operating characteristic (ROC) curve. The group with a CONUT score ≥ 3 was categorized as high CONUT, whereas the group with a CONUT score < 3 was categorized as low CONUT. The groups were compaired according to oncological outcomes and survival risk factors. Results: Cancer-specific survival (CSS) and overall survival (OS) were statistically significantly lower in the High CONUT group compared to the Low CONUT group (p < 0.001, p = 0.024, respectively). Age (HR: 1.02, 95% CI: 1.006-1.04, p = 0.011) and CONUT score (HR: 3.92, 95% CI: 2.66-5.77, p < 0.001) were revealed to be independent prognostic variables in the multivariate analysis for OS. Conclusion: The CONUT score was found to be an independent predictor of survival in patients with muscle-invasive bladder cancer in this study.